ASUHAN KEPERAWATAN PADA KLIEN DENGAN MASALAH RISIKO PERFUSI JARINGAN SEREBRAL TIDAK EFEKTIF DI KELURAHAN LIMO, KOTA DEPOK - Listi Aisah Patma Hasibuan (2023)
Background : Stroke is a condition that occurs due to a disturbance in the blood vessels located in the brain resulting in the death of tissue in the brain which then causes the sufferer to experience paralysis and even death (Fransisca, 2012). Methode : In this study a descriptive case study method was used because researchers wanted to intensively examine nursing care in stroke patients with a risk of brain tissue perfusion in Limo District, Depok City. Results and Discussion : Based on the assessment conducted on the client Ny. R with priority nursing diagnosis in the form of risk of ineffective cerebral perfusion. Conduct planning and implementation that focuses on monitoring vital signs, providing a head up position, regular Range of Motion (ROM) exercises. Nursing actions are carried out based on planning with the results of the evaluation of partially resolved nursing problems. Based on the criteria for the results, the client's condition has improved sufficiently, based on the results of blood pressure monitoring it is gradually improving, limb movements are developing gradually. It is expected that the nurse periodically monitors the client's blood pressure and helps the client position the head 30º towards the stroke client. The higher the MAP, the more likely the client will experience impaired cerebral perfusion which is ineffective and risky for the client himself. From the results of calculating the client's MAP with the calculation formula MAP = (2(DBP)+SBP)/3 equal to MAP = (2(84)+163)/3 = 110.33, and it can be concluded that if the higher the MAP, the client will the more at risk of experiencing impaired cerebral perfusion is ineffective and at bad risk for the client himself.